Validation of the Family Integration Experience Scale: Chronic Illness for the Portuguese language spoken in Brazil - Carolliny Rossi de Faria Ichikawa; Regina Szylit (Revista Latino-Americana de Enfermagem, 2024)
Objective: to conduct the cross-cultural adaptation and psychometric validation of the Family Integration Experience Scale: Chronic Illness in Brazilian Portuguese. Method: a methodological study divided into two stages. In the first stage, the Family Integration Experience Scale: Chronic Illness was cross-culturally adapted for Brazilian culture, when the scale was subjected to translations, back-translations, and a committee of judges - to verify the semantic, linguistic, and contextual equivalence between the original and translated items. The second step was to validate the scale in a sample of families of children and adolescents with chronic illnesses. The participants were 230 families of children with chronic illnesses attending the outpatient clinic of a tertiary public hospital with teaching and research characteristics. Results: internal consistency was tested using Cronbach’s alpha (0.81) and McDonald’s omega (0.81). Confirmatory factor analysis was also tested, and the model’s fit was acceptable for validation standards. Conclusion: the version of the Family Integration Experience Scale: Chronic Illness showed evidence of validation and can be considered a valid and reliable instrument in Brazilian culture. The Brazilian Portuguese version of the Family Integration Experience Scale: Chronic Illness can be used to measure the experience of family integration in chronic illness.